1998
DOI: 10.1515/cclm.1998.031
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Several Markers in the Progression to Acquired Immunodeficiency Syndrome

Abstract: Serum beta 2-microglobulin, neopterin, immunoglobulins A, G and M, adenosine deaminase and CD4+ lymphocyte count were evaluated as predictors of progression of HIV-1 infection to AIDS. A population of HIV-1 seropositive, initially asymptomatic men (n = 213) and women (n = 101) was followed up quarterly. We estimated the AIDS-free time using the actuarial method (median survival time 47.2 months). Cox proportional hazard analysis revealed that all markers studied were significant (p < 0.05) in relation to progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…21 The addition of neopterin values to the CD4+ count improves the predictive value for progression from HIV-1 infection to AIDS. 22 Neopterin levels can also provide a useful prognostic index for survival time in HIV-1 infection. 23 Neopterin levels have previously been investigated in acute anterior uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…21 The addition of neopterin values to the CD4+ count improves the predictive value for progression from HIV-1 infection to AIDS. 22 Neopterin levels can also provide a useful prognostic index for survival time in HIV-1 infection. 23 Neopterin levels have previously been investigated in acute anterior uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is also a place for more easily performed laboratory tests with similar predictive value as CD4 + cell counts. Neopterin and β2-microglobulin levels proved to be significant predictors of AIDS risk in HIV-1 seropositives136. The predictive value of both parameters is equal to CD4 + cell counts and both markers are significant joint predictors in addition to CD4 + cell counts.…”
Section: Surrogate Markers For Hiv Monitoringmentioning
confidence: 88%
“…To achieve a high sensitivity threshold, a judicious choice of HIV-1 gene targets, primers, and probes is critical. Updated versions of the NucliSens EasyQ and Roche Cobas Ampliprep/Cobas TaqMan HIV-1 tests were recently introduced in order to improve the ability of their former versions to amplify non-B subtypes135136.…”
Section: Viral Load Assaysmentioning
confidence: 99%
“…CD4 + cell count has been known for a long time now to be a marker for the progression of both HIV and FIV infection [12,23,24]. However it has recently been shown that CD4 is not the primary receptor for FIV, and that proliferation and infection of activated CD4 + T cells is instead facilitated via CD134 as the binding receptor [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a relationship has been described in which serum ADA correlated with retroviral infection in HIV infection [21]. ADA is also reported to be a useful marker of progression of HIV infection to AIDS in humans [15,24]. To our knowledge there is little or no information about ADA in the feline species in the literature.…”
mentioning
confidence: 99%